2019
DOI: 10.1111/ffe.13104
|View full text |Cite
|
Sign up to set email alerts
|

A general scenario of fish‐eye crack initiation on the life of high‐strength steels in the very high‐cycle fatigue regime

Abstract: When high‐strength steels are subjected to very high‐cycle fatigue loading, crack initiation site shifts from surfaces to the interior, and a fish‐eye forms on the fracture surface. Majority of the fatigue life is estimated to be associated with the formation of this internal crack morphology. In the present work, features of such internal cracks in two high‐strength steels are studied. Specifically, three initiation patterns are investigated. A general internal crack initiating scenario is proposed base on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The ridges on fatigue fracture surfaces (also known as ‘wing‐like structures’), 8 formed along the crack propagation direction, can be observed preferentially in low and medium carbon steels with a tempered martensite structure 14,52–54 . For the case of 42CrMo4‐tempered steel, investigated in present work, ridges are noticeable not only within a fisheye 55 but even on fatigue cracks initiated from the surface 34 .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The ridges on fatigue fracture surfaces (also known as ‘wing‐like structures’), 8 formed along the crack propagation direction, can be observed preferentially in low and medium carbon steels with a tempered martensite structure 14,52–54 . For the case of 42CrMo4‐tempered steel, investigated in present work, ridges are noticeable not only within a fisheye 55 but even on fatigue cracks initiated from the surface 34 .…”
Section: Discussionmentioning
confidence: 56%
“…Within the given material and stress conditions, fracture zone and related fatigue stage depend mostly on the effective stress intensity factor (SIF) range Δ K eff , which is a function of applied stress and crack length 6 . Below the threshold level of fatigue crack propagation, that is, Δ K th (4–5 MPa√m for high strength steels), 7,8 the fatigue lifetime is spent on the development of microcracks with an average crack growth rate (CGR) smaller than one atomic lattice period per cycle 9 . This fatigue stage is related to the fracture morphology called fine granular area (FGA) 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…The dependency of the fatigue crack propagation threshold ΔK th on the Young's modulus is well known from the literature. [61][62][63] Wang et al 64 showed for two high-strength steels a simplified equation to calculate the fatigue crack propagation threshold (ΔK th = 3.85 MPa√m) using the Young's modulus and the lattice spacing to describe the transition from the stage of crack initiation, where the FGA is formed, to the stage of short crack growth. The SIF of the microshrinkages investigated in this work showed much higher values (average of ΔK th = 7.0 ± 2.2 MPa√m), which is the explanation of missing FGA (see Section 4.2).…”
Section: Influence Of Temperaturementioning
confidence: 99%
“…The SIF of the microshrinkages investigated in this work showed much higher values (average of ΔK th = 7.0 ± 2.2 MPa√m), which is the explanation of missing FGA (see Section 4.2). Using the equation to calculate ΔK th by Wang et al 64 and the Young's modulus of G42CrMo4 leads to a reduction of ΔK th from RT to 773 K by 24%. Therefore, the transition from crack initiation to crack growth is particularly favoured at 773 K compared with the lower temperatures.…”
Section: Influence Of Temperaturementioning
confidence: 99%
“…For Ti6Al4V the abbreviation ‘rough area’ (RA) is also frequently used [ 7 , 8 ]. However, the areas introduced by the different terms do not necessarily correlate with each other [ 9 ]. Accordingly, the size of an ODA or GBF, detected in optical microscopy and ‘scanning electron microscopy’ (SEM), respectively, does not necessarily correspond to the FGA, which refers to the existence of a nanograin layer below the fracture surface.…”
Section: Introductionmentioning
confidence: 99%